Accuracy of DME/DME positioning in Ukrainian airspace - Остроумов, I. В. (Problems of Informatization and Control, 2013)
Availability of positioning by DME equipment in Ukrainian has been discussed. The horizontaldilution of precision coefficients for DME/DME navigation algorithm and HDOP calculation forUkrainian airspace have been represented. As a result accuracy of DME/DME positioning method hasbeen calculated.